Analisis Kondisi Fisik Atlet Unesa Women Football Club meliputi Daya Tahan, Kecepatan, Kelincahan, Kekuatan, dan Daya Ledak - Wina Arlina Putri Andini; Achmad Widodo; Indra Himawan Susanto; Mokhamad Nur Bawono (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
Athletic physical condition is a key factor in determining an athlete's performance during competitions. This study aims to assess the physical condition of Unesa Women FC athletes using a descriptive quantitative method, involving 20 athletes as the sample. Data was collected through a series of physical tests to measure various aspects of physical fitness, including aerobic endurance, speed, agility, leg strength, and explosive power. The tests conducted included the Multistage Fitness Test (MFT) for aerobic endurance, a 30-meter sprint for speed, Illinois Agility Run for agility, Leg Dynamometer for leg strength, and Jump MD for explosive power. The results of the study show that the average VO2Max of the athletes is 30.8 ml/kg/min, which falls into the "Poor" category. This indicates that the athletes' aerobic endurance has not yet reached the optimal standard required for competitive performance. The 30-meter sprint time recorded was 5.53 seconds, categorized as "Good," indicating that the athletes have adequate speed. However, the agility score obtained from the Illinois Agility Run was 21.97 seconds, classified as "Poor," suggesting that the athletes need to improve their agility for quicker movements on the field. The explosive power score, measured by the Jump MD test, was 45.75 cm, which also falls into the "Poor" category, while leg strength, measured using the Leg Dynamometer, resulted in a score of 57.47 kg, classified as "Very Poor." These findings indicate that most components of the physical condition of the Unesa Women FC athletes are still below optimal levels. Therefore, the study emphasizes the need for a more structured and targeted physical training program tailored to the individual needs of each athlete. A training program designed based on these test results will help improve the physical fitness components that are lacking and support the enhancement of their performance during competitions.